Genomic analysis of qnr-harbouring IncX plasmids and their transferability within different hosts under induced stress - Nohejl, Tomas; Valcek, Adam; Papousek, Ivo; Palkovicova, Jana; Wailan, Alexander M; Pratova, Hana; Minoia, Marco; Dolejska, Monika (BMC microbiology, 2022)
BACKGROUND: Conjugative plasmids play a major role in the dissemination of antibiotic resistance genes. Knowledge of the plasmid characteristics and behaviour can allow development of control strategies. Here we focus on the IncX group of plasmids carrying genes conferring quinolone resistance (PMQR), reporting their transfer and persistence within host bacteria of various genotypes under distinct conditions and levels of induced stress in form of temperature change and various concentrations of ciprofloxacin supplementation. METHODS: Complete nucleotide sequences were determined for eight qnr-carrying IncX-type plasmids, of IncX1 (3), IncX2 (3) and a hybrid IncX1-2 (2) types, recovered from Escherichia coli of various origins. This data was compared with further complete sequences of IncX1 and IncX2 plasmids carrying qnr genes (n = 41) retrieved from GenBank and phylogenetic tree was constructed. Representatives of IncX1 (pHP2) and IncX2 (p194) and their qnrS knockout mutants, were studied for influence of induced stress and genetic background on conjugative transfer and maintenance. RESULTS: A high level of IncX core-genome similarity was found in plasmids of animal, environmental and clinical origin. Significant differences were found between the individual IncX plasmids, with IncX1 subgroup plasmids showing higher conjugative transfer rates than IncX2 plasmids. Knockout of qnr modified transfer frequency of both plasmids. Two stresses applied simultaneously were needed to affect transfer rate of wildtype plasmids, whereas a single stress was sufficient to affect the IncX ΔqnrS plasmids. The conjugative transfer was shown to be biased towards the host phylogenetic proximity. A long-term cultivation experiment pointed out the persistence of IncX plasmids in the antibiotic-free environment. CONCLUSIONS: The study indicated the stimulating effect of ciprofloxacin supplementation on the plasmid transfer that can be nullified by the carriage of a single PMQR gene. The findings present the significant properties and behaviour of IncX plasmids carrying antibiotic resistance genes that are likely to play a role in their dissemination and stability in bacterial populations.
Keywords: Animals; Escherichia coli; Conjugation, Genetic; Genomics; Anti-Bacterial Agents; proteiny z Escherichia coli; bakteriální léková rezistence; konjugace genetická; ciprofloxacin; Phylogeny; plazmidy; Ciprofloxacin; Plasmids; zvířata; antibakteriální látky; fylogeneze; Drug Resistance, Bacterial; Escherichia coli Proteins; genomika